Characterizing Heparin Tetrasaccharides Binding to Amyloid-Beta Peptide - Zhou, Xiang; Wang, Yuanyuan; Zheng, Wei; Deng, Guangxiu; Wang, Fuyi; Jin, Lan (Frontiers in Molecular Biosciences, 2022)
The aggregation of β-amyloid peptide (Aβ) is responsible for Alzheimer’s disease (AD). Heparin can either promote or inhibit Aβ aggregation. The sulfation pattern and chain size determine its binding affinity and its role. Using 2D-NMR analysis and molecular modelling, the minimum binding motif of heparin to Aβ was deter-mined to be HexA-GlcNS-IdoA2S-GlcNS6S. Iduronic acid epimerization and 6-O-sulfation are key factors for the binding affinity, while 3-O-sulfation of heparin is not involved in the binding to Aβ. Hydrogen-deuterium exchange mass spectrometry (HDX-MS) was used to study the glycosaminoglycan (GAG)-peptide complex and identified V12HHQKL17 as the binding site of GAG at Aβ. Furthermore, an MTT assay was applied to evaluate the anti-Aβ fibril-formation function of heparin tetrasaccharide, and indicated that the heparin tetrasaccharide with the defined sequence represents a promising therapeutic agent for the treatment of AD.